Kelompok Basis Gerejani Dan Tantangan Sosio-Budaya Terhadap Penghayatan Perkawinan Katolik Masyarakat Urban - Ferdinandus Ngambut; Alphonsus Tjatur Raharso; Antonius Denny Firmanto (Vox Dei: Jurnal Teologi dan Pastoral, 2023)
The focus of this research is the socio-cultural influence and challenges of urban communities for the passion of marriage promises from Catholic couples and the importance of involvement in the ecclesiastical base group environment for the passion of marriage. Marriage for Catholics is a lifelong communion between a man and a woman and is open to the birth and education of a child. This study was conducted using a methodology between interviews and literature studies. Researchers conducted interviews with five Catholic couples who lived in one of the base environments of Ijen Parish, Diocese of Malang, namely the Santa Clara neighborhood. This research found that the socio-cultural life of urban society today is really a severe challenge for the marriage passion of Catholic families. Many of the lifestyles that develop in the socio-cultural context of urban societies today clash with the nature of marriage according to the Catholic Church. In the midst of these challenges, participation in ecclesiastical base groups is a great way to help couples stay true to their marital vows. The ecclesiastical base group became the place where they gained edification, shared, and supported each other in the light of God's word.